Nudging Higher Education Libraries: The Portuguese Recommendations - Costa, Teresa (2018)
This study aims to present the Recommendations for Higher Education Libraries in Portugal presented by the Working Group of Higher Education Libraries of the Portuguese Association of Librarians, Archivists and Documentalists. These recommendations intend to work as Guidelines and have emerged as the answer to the need to adapt libraries to the 21st century changes regarding Information and Knowledge Societies. In Portugal, Library Information Science (LIS) professionals have been attentive to the changes that have occurred in higher education, technologies, communication and information sharing. The impact of these changes has been remarkable, especially concerning the skills which librarians must develop to respond to different user needs, to the new management of information systems, to the growing importance of information literacy, to new publication systems and in everything that includes the management and dissemination of scientific and academic knowledge. The Working Group of Higher Education Libraries integrates librarians from several public and private Portuguese institutions of higher education (universities and polytechnics) and is committed to continue an updated debate through the lines of intervention set out for its mission. Although these Recommendations are intended for higher education institution librarians, they can be followed by all LIS professionals who wish to improve their professional skills, therefore they can be used as guidelines helping to create professional development opportunities. Their main focuses are to meet the strategic objectives of creating knowledge, sharing experiences, promoting the transfer of knowledge and improving the conception of policies regarding information and documentation, including information literacy.